(untitled) (Journal of Architectural Design, 2022)
In this article, miniatures by Kamoliddin Bekhzad and other artists of the Timurid and post-Timurid eras are considered as a source on the architecture of medieval baths. Depicting the external and internal structure and decoration of baths, they, along with historical sources and little-studied archival materials, can play an important role in restoring the former appearance of the interior and exterior of the medieval baths of Shakhrisabz.